Implementation of Appropriate Technology Polycrystalline Photovoltaic as New Renewable Alternative Energy in Public Street Lighting (PJU) at Pakuniran Probolinggo Area - Azhari, Muhammad Holqi Rizki; Handoko, Wahyu Tri; Falah, Moh. Zainul; Rahmat Busono, Milzam; Faraasyatul ‘Alam, Ghasa; Sucipto, Sucipto; Umam, Khotibul (CV. Creative Tugu Pena, 2023)
Public road lighting (PJU) in the Pakuniran area, Probolinggo, East Java, more precisely in Gondosuli Village, is not sufficient. An environment without street lighting will be like a dead zone and can occur in many cases of crime, and traffic accidents and will hurt social life at night. Therefore, the community service team at the State University of Malang (UM) through student service provided a solution to reaching the road by utilizing new, renewable energy from polycrystalline solar panels to turn on the lights at night. The results of observations and site surveys show that several points require PJU installation with polycrystalline technology. The implementation carried out in Gondosuli Village was carried out in several stages, namely: observation, preparation of PJU designs, training and maintenance, performance testing, and evaluation tools. This activity, which was completed within 2 months, resulted in 5 PJUs being placed at several points with minimal lighting conditions and received a positive response from the community. Keywords: Public Street Lighting, Polycrystalline Photovoltaic, Gondosuli Village